2020
DOI: 10.3390/polym12081676
|View full text |Cite
|
Sign up to set email alerts
|

Tribological and Mechanical Behavior of Graphite Composites of Polytetrafluoroethylene (PTFE) Irradiated by the Electron Beam

Abstract: This research investigated the effect of irradiation with an electron beam energy of 10 MeV in doses of 26–156 kGy on polytetrafluoroethylene (PTFE) with a 15% and 20% graphite additive. The research has shown that mechanical (compression strength, hardness, and Young’s modulus) and sclerometric (coefficient of wear micromechanism and coefficient of resistance to wear) properties improve and tribological wear decreases as graphite content increases. Electron beam irradiation increases the degree of crystallini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…After UV irradiation ( Figure 12 b), the surface of the sample was smoother, and the values of the average roughness Ra and the root mean square Rq of the sample showed a decreasing trend. This rule is consistent with the previous research results [ 32 , 33 , 34 ], indicating that the UV irradiation device described in this paper can effectively carry out the related research work on the influence of ground simulated space UV irradiation on the surface properties of materials.…”
Section: Resultssupporting
confidence: 92%
“…After UV irradiation ( Figure 12 b), the surface of the sample was smoother, and the values of the average roughness Ra and the root mean square Rq of the sample showed a decreasing trend. This rule is consistent with the previous research results [ 32 , 33 , 34 ], indicating that the UV irradiation device described in this paper can effectively carry out the related research work on the influence of ground simulated space UV irradiation on the surface properties of materials.…”
Section: Resultssupporting
confidence: 92%
“…Other researchers have also enhanced the mechanical properties of PTFE composites through irradiation modification. Barylski et al investigated the impact of 10 MeV electron beam irradiation at doses ranging from 26 to 156 kGy on PTFE with a graphite additive content of 15% and 20% 19 . Lv et al reported the utilization of proton irradiation for modifying CF‐reinforced PTFE composites 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The addition of bronze affects the electrical conductivity and thermal volume. While the composites with coke content are produced to reduce flow under load, increase hardness and thermal conductivity [ 7 , 8 ]. In the work of Conte et.…”
Section: Introductionmentioning
confidence: 99%